2002
DOI: 10.1086/344069
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Radio Properties of Extragalactic Sources Observed by the FIRST Survey and the Sloan Digital Sky Survey

Abstract: We discuss the optical and radio properties of ∼30,000 FIRST (radio, 20 cm, sensitive to 1 mJy) sources positionally associated within 1.5 arcsec with an SDSS (optical, sensitive to r * ∼22.2) source in 1230 deg 2 of sky. The matched sample represents ∼30% of the 108,000 FIRST sources and 0.1% of the 2.5 × 10 7 SDSS sources in the studied region. SDSS spectra are available for 4,300 galaxies and 1,154 quasars from the matched sample, and for a control sample of 140,000 galaxies and 20,000 quasars in 1030 deg 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
474
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(525 citation statements)
references
References 66 publications
43
474
8
Order By: Relevance
“…By definition, only the radio-loud quasars will be targeted by this approach, so that the sample in itself is not complete (see, e.g., Urry & Padovani 1995;Sikora et al 2007, for a description of the radio emission from quasars and the empirical observations of the two sub-populations, respectively). Two recent radio selections of optical spatially unresolved quasars (Ivezić et al 2002;Baloković et al 2012) used data from the Faint Images of the Radio Sky at Twenty centimeters (FIRST; Becker et al 1995) mission together with the SDSS program. A similar approach was executed based on source detection with the FIRST matched to the NIR counterparts of the Two Micron All Sky Survey (2MASS; Skrutskie et al 2006) by Glikman et al (2007Glikman et al ( , 2012; Urrutia et al (2009).…”
Section: Radio Detectionmentioning
confidence: 99%
“…By definition, only the radio-loud quasars will be targeted by this approach, so that the sample in itself is not complete (see, e.g., Urry & Padovani 1995;Sikora et al 2007, for a description of the radio emission from quasars and the empirical observations of the two sub-populations, respectively). Two recent radio selections of optical spatially unresolved quasars (Ivezić et al 2002;Baloković et al 2012) used data from the Faint Images of the Radio Sky at Twenty centimeters (FIRST; Becker et al 1995) mission together with the SDSS program. A similar approach was executed based on source detection with the FIRST matched to the NIR counterparts of the Two Micron All Sky Survey (2MASS; Skrutskie et al 2006) by Glikman et al (2007Glikman et al ( , 2012; Urrutia et al (2009).…”
Section: Radio Detectionmentioning
confidence: 99%
“…As an observational proof of this scenario, Ivezić et al (2002) have shown that a sample of optically unresolved radio sources from the FIRST survey has bluer colors than do other SDSS objects, and Richards et al (2002) find that the SDSS quasar candidates -which are likely to have a radio counterpart -display blue colors, especially at z > 1, indicative of ongoing star formation. To understand the importance of the AGN-feedback in the current scenarios of galaxy evolution, a study of the AGN populations, the properties of the host galaxies, and the physical mechanisms that trigger the production of the emission lines or the radio-activity, is necessary.…”
Section: Introductionmentioning
confidence: 97%
“…Obric et al (2006) find strong correlations between the fraction of detected AGNs at other wavelengths and optical properties such as flux, colors, and emission-line strengths. Ivezić et al (2002) discuss the optical and radio properties of ∼30 000 FIRST (Becker et al 1995) sources positionally associated with a SDSS source by analyzing their colors, while Best et al (2005) compare the optical survey to both FIRST and NVSS radio surveys in order to derive the local radio luminosity functions of radioloud AGNs and star-forming galaxies. In the SDSS Early Data Release (Ivezić et al 2002), ∼70% of FIRST sources do not have an optical counterpart within 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This division into RLQs and RQQs still remains a point of discussion. Some authors advocate the idea that radio-loudness (R, radio-to-optical flux ratio) distribution for optical-selected quasars is bimodal (Kellermann et al 1989;Miller et al 1990;Ivezić et al 2002;Jiang et al 2007a), while others have confirmed a very broad range for the radioloudness parameter, questioning its bimodality nature (Cirasuolo et al 2003;Singal et al 2011Singal et al , 2013). …”
Section: Introductionmentioning
confidence: 99%